India [sic] Woman, Trinidad, B.W.I. - (:unkn) unknown ([Printed in Germany], 2009)
Hand painted image of an East Indian woman in traditional wear. Stamped on the back of the postcard is "Tourist Inquiry Bureau, Trinidad, B.W.I."
Colour: Red, Yellow, Green and White Hues; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; East Indians--Trinidad and Tobago; Nose rings--India